2015
DOI: 10.1088/1612-2011/13/2/025603
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface boiling in sub-threshold damage and above-threshold spallation of bulk aluminum and gold by single femtosecond laser pulses

Abstract: The sub and near-threshold topographic signatures of the spallation of nanometer-thick melt layers during single-shot femtosecond laser ablation of bulk aluminum and gold were experimentally observed for the first time, using scanning electron microscopy with high spatial resolution. The novel ablative nanofeatures—sub-threshold boiling nanopits, the partially detached ultrathin solidified melt layer, and the lamellar surface structure under the layer along the spallative crater border, as well as the foam-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…[28,29] First explanations connecting the RSS and foaming/rupture of foam and fast (before their disappearance thanks to surface tension) freezing of the cellular capillary remnants of foam (the remnants are: membranes, jets, and droplets) were given in ref. [32][33][34][35][36]. [32][33][34][35][36].…”
Section: Structure Of High-entropy Layer According To MDmentioning
confidence: 99%
“…[28,29] First explanations connecting the RSS and foaming/rupture of foam and fast (before their disappearance thanks to surface tension) freezing of the cellular capillary remnants of foam (the remnants are: membranes, jets, and droplets) were given in ref. [32][33][34][35][36]. [32][33][34][35][36].…”
Section: Structure Of High-entropy Layer According To MDmentioning
confidence: 99%
“…This picture is also supported by other studies on metals and dielectrics. Corresponding mechanisms were discussed for Ag, Au, and Ti under high fluence excitation [39,40], and for volume structures in glasses [42,71] (where surface plasmons, however, may be replaced by the coupling of many local plasmons). The ripple formation at the surface of fused silica is explained by the interplay of plasmons and incubation effects (accumulation of defect sites) [72].…”
Section: Initial Pulse (N = 1)mentioning
confidence: 99%
“…For metals like Ti, Al, and Au, it was shown that nanoscale surface boiling plays a role in sub-threshold damage, as well as above-threshold spallation by femtosecond laser pulses [39,40]. Although thermal material modification and rearrangement were detected at different time scales compared to the exciting light pulses, the ripple formation is significantly influenced by plasmons initially induced by the ultrafast laser pulses [39]. These findings indicate that a combination of sub-surface bubble generation and plasmon-related spatially periodical energy insertion results in the generation of isolated or merged nanovoids, depending on the fluence.…”
Section: Introductionmentioning
confidence: 99%
“…The polarization dependence of LIPSS formation [90] also confirms a plasmonic mechanism. Thermal material modification and rearrangement appear at later time scales but are strongly influenced by plasmons [91]. The ripple orientation, however, can be parallel or perpendicular to the polarization vector so that the scenario seems to be complex in detail (e.g.…”
Section: Laser-induced Periodic Surface Structures (Lipss)mentioning
confidence: 99%